Application of bioregulators for banana cv. Williams macro-propagation under thermal chamber. - Cedeño-García, Galo (2016)
The objective of this research was to evaluate the prolific response of corms of banana cv. Williams to the application of 6-Benzylaminopurine (6-BAP) and a biostimulant based on algae extract, under thermal chamber conditions. The trial was carried out from November 2013 to April 2014 at “La Teodomira” experimental farm of the Technical University of Manabí in Ecuador. The treatments were 6-benzylaminopurine (6-BAP) at concentrations of 0, 20, 40, and 80 mg/l, and a biostimulant based on algae extract at doses of 0, 20, 40, and 80 ml/corm. Benzylaminopurine was applied in the corm and the biostimulant was applied in drench. The design used was a randomized complete block with A x B factorial treatment where 6-BAP and the biostimulant were the factors; the treatments were replicated four times, for a total of 64 experimental units. Significant differences (p≤0.0001) were detected for 6-BAP factor where the higher multiplication rate was obtained at the concentration of 40 mg/l with 47.28 plantlets/corm. There were no significant differences (p≥0.9167) neither for the biostimulant nor for the 6-BAP x biostimulant interaction (p≥0.3789). Callus tissue formation was evident from first generation (R1) sprouts. At the concentration of 80 mg/l of 6-BAP, the presence of abnormal plantlets, especially coming from callus tissue, was observed.